Negotiating Identity and Power in Premodern Deccan: A Biographical Analysis of Afāqī Noble Afżal Khān Shīrāzī - G. Ahmad Raza (PC Ikatan Sarjana Nahdlatul Ulama Ponorogo, 2025)
This article primarily aims to explore the career of Mīr Ghiyāṯ-al-Dīn Shīrāzī by examining his identity and contributions to the ‛Ādil Shāhī Sultanate in Medieval Deccan. This study ameliorates the qualitative research methodology that focuses on the identity and the agency of individuals as a major factor that plays a significant role in shaping the personality and achieving the targets even when the opponent group of different backgrounds challenged and fiercely opposed. This research found Shīrāzī’s career very significant as it helps us in understanding the migration of elites and the networks of intellectuals within the medieval Persianate worlds that fostered new political and cultural prospects in premodern Deccan. It discovered extreme disagreements among nobles having diverse identities that derived them to play identity politics in order to ascertain their interests in premodern Deccan. The identity politics gave birth to the emergence of factionalism and sectarianism in the imperial court of the ‛Ādil Shāhī Sultanate. Consequently, ‛Ādil Shāhī rulers had to make state policies taking influences of the dominant group into their consideration. Accordingly, nobles used to adjust their loyalty and support in accordance to the rulers’ ideology and policies. In this context, the identity politics made a ruler and his noble interdependent. This study revealed that the regional identity was more effective than the politics of religious identity in premodern South Asia.